Rancang Bangun Inkubator Untuk Pengamatan Sorpsi Isotermis Berbasis Kaidah Exfert - Hartono, Hartono; Muhidong, Junaedi; Ikbal (Jurnal Agritechno, 2023)
The isotherm shorpsi curve is essential for estimating drying time, packaging, and material stability during storage. Based on the static method, the equilibrium moisture content of the material is obtained in a state of still air at a constant temperature. This research aims to make an incubator with constant temperature control. The method used in this study consisted of several stages, namely the design and assembly of the device, sensor calibration, and temperature rise testing. The results of the calibration of the tool show an average value of R2 = 0.998. This value indicates that the temperature readings from the sensor used with the mercury thermometer readings are very close. The temperature rise in the storage room experiences a constant increase until it reaches the setting point.